COMMON BONDS? ON THE INTERSECTION OF CLASS, RACE AND GENDER IN THE LIVES OF U.S. WOMEN - Adelman, Miriam (Revista de Sociologia e Política, 1997)
This paper reviews historical and sociological literature exploring the interaction of class, race and gender in the lives of U.S. women. It addresses current debates on diversity and ‘women’s condition ’, emphasizing the ways in which patriarchy fuses with class and race inequality, creating divergent experiences of oppression.